Explaining and Overcoming Marginalization in Education: Ethnic/Language Minorities in Peru - Cueto, S; Guerrero, G; León, J; Seguin, E (Palgrave Macmillan, 2012)
In the past few decades, education in Peru has shown increased enrolment, especially in primary schools, but low achievement as measured by national and international standard tests in reading comprehension and mathematics. However, averages hide wide disparities in educational outcomes, which are often influenced by individual and family characteristics. Among these, coming from a family that speaks an indigenous language has been shown to be a significant predictor of low educational outcomes as compared to coming from a Spanish-speaking family (Cueto 2007: 425–6).2 In this chapter, we present and discuss evidence of this trend in Peru, suggesting policies to overcome existing inequalities.